Optimization and design of electromechanical control automation based on dual motor control algorithm - Lu, Wei (Frontiers in Mechanical Engineering, 2024)
IntroductionIn response to the high demand for dynamic characteristics and control in current electromechanical automatic control systems.MethodsThis study first analyzes the dual motor system. A novel electromechanical control automation model based on a dual motor control algorithm is proposed through the control strategy of dual motor backlash elimination and digital proportional integral derivative control algorithm.Results and DiscussionThe results indicated that the optimization of the model had a promoting effect on the control performance of the electromechanical automatic control system. Compared with other popular electromechanical control automation models of the same type, the performance of the research method was the best. During the no-load start-up phase, the maximum tracking error and synchronization error speed of the proposed new electromechanical control automation model showed a significant decreasing trend, with the maximum synchronization error between the two motors being only 0.02%. Under steady-state sudden load, the research model could reach a stable state within 3 s, with errors within ±5%.ConclusionIn summary, combining the dual motor control algorithm with the electromechanical control automation method can provide a theoretical basis and practical guidance for designing and implementing efficient dual motor electromechanical control systems.